The Impact of Promotion and Price on Purchase Decisions with Buying Interest as a Mediating Variable in Celosia Flower Garden Bandungan - Nuraeini, Lu’lu’; Nurhayati, Nurhayati (Economics and Business International Conference Proceeding, 2024)
The research purpose to analyze the influence of price and promotion buying interest in the Celosia Flower Garden in Bandungan. The population in this sample is respondents who have visited the Celosia Flower Garden Bandungan with an age category over 17 years old. The research method used is the analysis tool used in this study is the Structural Equation Modeling (SEM) analysis tool.The results of this study show that Promotion has a positive and significant effect on Buying Interest. Price has a positive and significant effect on buying interest. Buying interest has a positive and significant effect on purchase decisions with. Promotions have a positive and significant effect on purchase decisions. Price has a positive and significant effect on the purchase decision